Corporate Governance Practices And Audit Quality: An Empirical Study Of The Listed Companies In Egypt - Soliman, Mohamed Moustafa; Elsalam, Mohamed Abd (Zenodo, 2012)
Recent financial international scandals around the world have led to a number of investigations into the effectiveness of corporate governance practices and audit quality. Although evidence of corporate governance practices and audit quality exists from developed economies, very scanty studies have been conducted in Egypt where corporate governance is just evolving. Therefore, this study provides evidence on the effectiveness of corporate governance practices and audit quality from a developing country. The data for analysis are gathered from the top 50 most active companies in the Egyptian Stock Exchange, covering the three year period 2007-2009. Logistic regression was used in investigating the questions that were raised in the study. Findings from the study show that board independence; CEO duality and audit committees significantly have relationship with audit quality. The results also, indicate that institutional investor and managerial ownership have no significantly relationship with audit quality. Evidence also exist that size of the company; complexity and business leverage are important factors in audit quality for companies quoted on the Egypt Stock Exchange. : {"references": ["Adeyemi, S. B, and Temitope O. F., \"Audit Quality, Corporate\nGovernance and Firm Characteristics in Nigeria\", International Journal\nof Business and Management, Vol. 5, No. 5, P. 169- 179, 2010.", "Saudagaran, S. M., \"The Accounting World Post-Enron, Tyco, Vivendi,\nWorldcom, Xerox: Reflections on Being Part of the Solution\",\nMalaysian Accounting Review, Vol. 2, No.1, P. 2-12, 2003.", "DeAngelo, L.E., \"Auditor size and audit quality\", Journal of Accounting\nand Economics, Vol. 3, No. 3, pp. 99-183, 1981.", "Becker, C., Defond, M., Jiambalvo, J., and K. Subramanyam, \"The effect\nof audit quality on earnings management\", Contemporary accounting\nresearch, Vol.15, pp.1-24, 1998.", "Piot, C., \"Auditor Reputation and Model of Governance: A Comparison\nof France, Germany and Canada\", International Journal of Auditing,\nVol. 9, P. 21-44, 2005.", "Fan, J. P. H. and T. J. Wong, \"Do External Auditors Perform a\nCorporate Governance Role in Emerging Markets? Evidence from East\nAsia\", Journal of Accounting Research, Vol. 43, No. 1, P. 35-72, 2004.", "Ebaid, I. E.,\" Corporate governance practices and auditor-s client\nacceptance decision: empirical evidence from Egypt\", Corporate\nGovernance, Vol. 11, No. 2, P. 171-183, 2011.", "Sharma, D.S., Boo, E. and Sharma, V.D. \u00d4\u00c7\u00ff\u00d4\u00c7\u00ffThe impact of non-mandatory\ncorporate governance on auditors- client acceptance, risk and planning\njudgments--, Accounting and Business Research, Vol. 38 No. 2, p. 105-20, 2008.", "Craswell, A., J., Francis, and S., Taylor, \"Auditor brand name\nreputations and industry specializations\", Journal of Accounting and\nEconomics, Vol. 20, No. 3, pp. 297-322, 1995.\n[10] Sainty, B.J., Taylor, G.K. and Williams, D.D., \"Investor dissatisfaction\ntoward auditors\", Journal of Accounting, Auditing and Finance, Vol.17,\nNo.2, 2002.\n[11] Kane, G. D., and. U. Velury, \"The Role of Institutional Ownership in\nthe Market for Auditing Services: An Empirical Envestigation\", Journal\nof Business Research, Vol. 57, (September), pp. 976-983, 2004.\n[12] Carcello, J.V., and Nagy. A.L., \"Client size, auditor specialization and\nfraudulent financial reporting\", Managerial Auditing Journal, Vol.19,\nNo.5, 2004.\n[13] Simunic, D.A. and Stein, M.T., \"Product Differentiation in Auditing: Auditor Choice in the Market for Unseasoned New Issues\", Canadian\nCertified General Accountants- Research Foundation Monograph, 1987.\n[14] DeZoort, F.T., Hermanson, D.R., Archambeault, D.S. and Reed, S.A.,\n\u00d4\u00c7\u00ff\u00d4\u00c7\u00ffAudit committee effectiveness: a synthesis of the empirical audit\ncommittee literature--, Journal of Accounting Literature, Vol. 21, p. 38-\n75, 2002.\n[15] Anderson, R.C., Mansi, S.A. and Reeb, D.M., \u00d4\u00c7\u00ff\u00d4\u00c7\u00ffAmerican Institute of\nCertified Public Accountants AICPA professional standards, Statement\non Quality Control Standards, American Institute of Certified Public\nAccountants, New York--, Journal of Accounting and Economics, Vol.\n37 No. 2, p. 315-42, 2004.\n[16] Klein, A., \u00d4\u00c7\u00ff\u00d4\u00c7\u00ffAudit committee, board of directors characteristics, and\nearnings management--, Journal of Accounting and Economics, Vol. 33\nNo. 2, p. 375-400, 2002.\n[17] Blue Ribbon Committee, Report and recommendations of the Blue Ribbon Committee on improving the effectiveness of corporate audit committee, New York: NYSE and NASD, 1999.\n[18] Public Oversight Board. Strengthening the professionalism of the\nindependent auditor. Stamford, CT: POB, 1994.\n[19] O-Sullivan, N., \"The impact of board composition and ownership on\naudit quality: evidence from large UK companies\", The British\nAccounting Review, Vol. 32, No.4, P.397- 414, 2000.\n[20] Salleh, Z., Stewart, J., & Manson, S., \"The Impact of Board Composition\nand Ethnicity on Audit Quality: Evidence from Malaysian Companies\", Malaysian Accounting Review, Vol. 5, No. 2, P. 61-83, 2006.\n[21] Yermack, D., \"Higher Market Valuation of Companies with Small\nBoards of Directors\", Journal of Financial Economics, Vol.40, No. 2, P.\n185-212, 1996.\n[22] Pi, L., & Timme, S., \"Corporate Control and Bank Efficiency\", Journal\nof Banking and Finance, Vol. 17, No.2, P. 515-530, 1993.\n[23] Lin, Z. J., and M. Liu, \"The Impact of Corporate Governance on Auditor\nChoice: Evidence from China\", Journal of International Accounting,\nAuditing and Taxation, Vol. 18, No. 1, pp. 44-59, 2009.\n[24] Mitra, S., Hossain, M., & Deis, D.R., \"The empirical relationship between ownership characteristics and audit fees\", Rev Quant Finance Acc, Vol. 28, P. 257-285, 2007.\n[25] Chan, K. H., Lin. K. Z., and F. Zhang, \"On the Association between\nChanges in Corporate Ownership and Changes in Auditor Quality in a Transitional Economy\", Journal of International Accounting Research,\nVol. 6, No. 1, pp. 19-36, 2007.\n[26] Niskanen, M., Karjalainen, J., and J. Niskanen, \"Demand for Audit\nQuality in Small Private Firms: Evidence on Ownership Effects\",\nAvailable at: http://ssrn.com/abstract=1324599. 2009.\n[27] Mahdavi, G., Mohammed, M., Fahime, E. & Mehdi, S. \"The Impact of\nCorporate Governance on Auditor Choice\", International Research\nJournal of Finance and Economics, Vol. 68, P. 129-139. 2011.\n[28] McMullen, D.A., ''Audit committee performance: an investigation of\nthe consequences associated with audit committees'', Auditing: A\nJournal of Practice & Theory, Vol. 15 No. 1, pp. 1-28, 1996.\n[29] Mitchell, V. Z., Singh, H.and Singh, I. \"Association between\nindependent audit committee members' human-resource features and\nunderpricing\", Journal of Human Resource Costing & Accounting. Vol.\n12 No. 3, P. 179-212, 2008.\n[30] Abd-Elsalam, O.H., & Weetman, P., \"Introducing International\nAccounting Standards to an Emerging Capital Market: Relative\nFamiliarity and Language effect in Egypt\", Journal of International\nAccounting, Auditing & Taxation, Vol.12, p: 63-84, 2003.\n[31] Zeitun, R. and Tian, G., \"Does ownership affect a firm's performance\nand default risk in Jordan?\", Corporate Governance, Vol.7 No. 1, P. 66-\n82, 2007.\n[32] Beasley, M. S., \"An empirical analysis of the relation between the board\nof director composition and financial statement fraud\". Accounting\nReview, Vol. 71, No.10, P. 443-465, 1996.\n[33] Wan, Z.W.A., Shahnaz, I., & Nurasyikin, J., \"The impact of board\ncomposition, ownership and CEO duality on audit quality\". Malaysian\nAccounting Review, Vol. 7, No. 2, P. 1-22, 2008.\n[34] Tabachnick, B & Fidell, L., Using multivariate statistics, 3rd edition,\nNew York, Harper Collins, 1996."]}